Successful medical management of a Nocardia farcinica multiloculated pontine abscess. (5th December 2013) - Chow, Felicia C; Marson, Alexander; Liu, Catherine
Abstract : A 60-year-old man on chronic corticosteroids developed diplopia, gait instability and facial weakness. Brain MRI revealed a multiloculated pontine lesion. Cerebrospinal fluid (CSF) analysis demonstrated a neutrophil-predominant pleocytosis with elevated protein and low glucose. CSF cultures were negative, as was an extensive infectious diseases evaluation. Neurosurgical intervention was deferred in favour of empiric antimicrobial therapy due to the lesion's inaccessible location. After discontinuation of therapy, the patient reported a severe headache. A subsequent MRI demonstrated intraventricular pus. CSF culture grew Nocardia farcinica. The patient received parenteral therapy followed by oral trimethoprim-sulfamethoxazole. At 9 months, he is symptom free. This case illustrates the importance of including Nocardia in the differential diagnosis of brainstem abscesses, especially in immunocompromised patients. The availability of antimicrobial agents with excellent Nocardia activity and CSF penetration may enable treatment of brainstem abscesses for which surgical intervention has traditionally been considered necessary with medical management alone.